UTM graduating students' perceptions on the task of the oral interaction tecs - Chu, Shean Yin, 1991- author; Masdinah Alauyah Md. Yusof, supervisor; Fakulti Pendidikan (2015)
Project Paper (Sarjana Muda Sains serta Pendidikan (Pengajaran Bahasa Inggeris sebagai Bahasa Kedua)) - Universiti Teknologi Malaysia, 2015